Concise review: Clinical programs of stem cell therapies for liver and pancreas. (28th October 2013) - Lanzoni, Giacomo; Oikawa, Tsunekazu; Wang, Yunfang; Cui, Cai‐Bin; Carpino, Guido; Cardinale, Vincenzo; Gerber, David; Gabriel, Mara; Dominguez‐Bendala, Juan; Furth, Mark E.; Gaudio, Eugenio; Alvaro, Domenico; et al.
Abstract: Regenerative medicine is transitioning into clinical programs using stem/progenitor cell therapies for repair of damaged organs. We summarize those for liver and pancreas, organs that share endodermal stem cell populations, biliary tree stem cells (hBTSCs), located in peribiliary glands. They are precursors to hepatic stem/progenitors in canals of Hering and to committed progenitors in pancreatic duct glands. They give rise to maturational lineages along a radial axis within bile duct walls and a proximal‐to‐distal axis starting at the duodenum and ending with mature cells in the liver or pancreas. Clinical trials have been ongoing for years assessing effects of determined stem cells (fetal‐liver‐derived hepatic stem/progenitors) transplanted into the hepatic artery of patients with various liver diseases. Immunosuppression was not required. Control subjects, those given standard of care for a given condition, all died within a year or deteriorated in their liver functions. Subjects transplanted with 100‐150 million hepatic stem/progenitor cells had improved liver functions and survival extending for several years. Full evaluations of safety and efficacy of transplants are still in progress. Determined stem cell therapies for diabetes using hBTSCs remain to be explored but are likely to occur following ongoing preclinical studies. In addition, mesenchymal stem cells (MSCs) and hematopoietic stem cells (HSCs) are being used for patients with chronic liver conditions or with diabetes. MSCs have demonstrated significant effects through paracrine signaling of trophic and immunomodulatory factors, and there is limited evidence for inefficient lineage restriction into mature parenchymal or islet cells. HSCs' effects are primarily via modulation of immune mechanisms. Stem Cells 2013;31:2047–2060